STRATEGI PENDISIPLINAN KEMBALI UNTUK MENANGGULANGI KESEMRAWUTAN DALAM KEHIDUPAN NASIONAL DEWASA INI - Ramses Purba; Muhammad Solly Lubis; Suhaidi Suhaidi; Faisal Akbar Nasution (Universitas Sumatera Utara, 2015)
ABSTRACT Law is a part of the system of national life. Therefore, the law is a device that needs to be reviewed and developed in order to discipline the back (redisciplineering) or curb long-term national scale / area. Its targets are disciplining the working procedures of the relevant authorities so that appropriate and consistent based on two aspects. This is an approach to the discipline of work or task. Discipline back chaos in the system of government in the State of Indonesia is very necessary because of Discipline within the scope are essentially stateless We have not had any practical experience with a new model after the 1945 amendment so weak presidential system. The Government adhered to the legal / state authorities in Indonesia are not in accordance with the basic state and can be assessed pragmatic, because the characters responsive legal products include: reflecting a sense of justice and meet the expectations of society, government / state officials have not met the applicable law in Indonesia, because the legal issues The most frequent and entrenched in this country is the inconsistency of the law enforcement officers of the law and legal regulations and are written clearly in the legislation. Keywords: Strategy, Discipline, National